Análisis de polimorfismos en los genes TP53 y MDM2 e leucemia linfocítica crónica - Mercado Guzmán, Zema Verónica (2019)
Chronic lymphocytic leukemia (CLL) is the most frequent adult leukemia in western countries. It is associated with a variety of chromosomal and molecular alterations, which may be associated with clinical and evolutionary features of the disease. Among these, mutations of TP53 gene or deletion 17p [del(17p13)], are associated with inactivation of the p53 pathway, exhibiting an adverse prognosis. The frequency of TP53 mutations is relatively low in newly diagnosed CLL patients, but increases significantly with disease progression. TP53 gene plays a central role in cancer suppression and the maintenance of genome stability, controlling DNA damage response, proliferation and apoptosis. Different authors have reported that polymorphisms in TP53 or its regulators MDM2 or NQO1 may also lead to the inactivation of the p53 signaling pathway, being its study in CLL of great interest since it could play an important role in the development and clinical evolution of patients.\nThe aim of this work was to study the relationship of polymorphisms in genes of the p53 pathway with susceptibility and prognostic factors in Argentine patients with CLL. We have analyzed 89 patients and 122 healthy controls. Three polymorphisms in TP53: SNP213 G>C (rs1042522), IVS3 16 bp indel (rs17878362) and IVS6+62A>G (rs1625895); 2 in MDM2: SNP309T>G (rs2279744), MDM2 indel1518 (rs3730485) and SNP NQO1 609C>T (rs1800566) were studied by PCR methods. Analysis of genetic models by logistic regression has shown that the polymorphisms studied are not associated with the risk of developing CLL. The TP53 213-CC (OR=6.98, CI 1.25-38.9, p=0.016) and MDM2 309-GG (OR=8.97, CI 11.55-52.0, p=0.007) genotypes have been associated with increased risk of abnormal karyotypes. In addition, the TP53 213-CC, TP53 IVS3-ins/ins, MDM2 309-GG and NQO1 609-TT genotypes represented an increased risk for del(17p13). Our data indicate that genetic variability in the p53 pathway does not modulate the risk of developing CLL but it is related to the acquisition of chromosomal alterations specific to the pathology. Attenuation of the p53 pathway due to variant genotypes probably leads to the failure of DNA repair resulting in genomic instability, which in turn would contribute to the emergence of specific CLL chromosomal alterations.